Ages of Anxiety : Historical and Transnational Perspectives on Juvenile Justice - Tanenhaus, David Spinoza; Bush, William S. (1967- ...) (Book collections on Project MUSE.)
Presentation de l'editeur : "Ages of Anxiety presents six case studies of juvenile justice policy in the twentieth century from around the world, adding context to the urgent and international conversation about youth, crime, and justice. By focusing on magistrates, social workers, probation and police officers, and youth themselves, editors William S. Bush and David S. Tanenhaus highlight the role of ordinary people as meaningful and consequential historical actors. After providing an international perspective on the social history of ideas about how children are different from adults, the contributors explain why those differences should matter for the administration of justice. They examine how reformers used the idea of modernization to build and legitimize juvenile justice systems in Europe and Mexico, and present histories of policing and punishing youth crime. Ages of Anxiety introduces a new theoretical model for interpreting historical research to demonstrate the usefulness of social histories of children and youth for policy analysis and decision-making in the twenty-first century. Shedding new light on the substantive aims of the juvenile court, the book is a historically informed perspective on the critical topic of youth, crime, and justice."